Relationship between stroke and compliance of antihypertensive medication - Roy, Debashis; Shahidulla, Muhammad; Morshed, Mamun; Roy, Chayan; Sabuz, Mahmudul Hasan; Chowdhury, Supta (International Journal of Research in Medical Sciences, 2024)
Background: Stroke is a leading cause of death and long-term disability globally, with hypertension being a key modifiable risk factor. Effective management of hypertension through medication compliance is crucial for reducing the risk of both initial and recurrent strokes. However, non-compliance with antihypertensive medication is a common challenge, particularly in resource-constrained countries like Bangladesh, where awareness and access to healthcare can be limited. This study aimed to investigate the relationship between antihypertensive medication compliance and the incidence of stroke, as well as the risk of stroke recurrence, in hypertensive patients admitted to Dhaka Medical College Hospital. Methods: A descriptive cross-sectional study was conducted between March and August 2010, involving 100 stroke patients diagnosed clinically and confirmed by CT scan. Data on patients’ hypertension status, medication adherence, and stroke history were collected through interviews and medical record reviews. Statistical analysis was conducted using SPSS software (Version 12) to explore the relationship between compliance and stroke occurrence. Results: From 100 stroke patients, 65% were previously diagnosed with hypertension. Among these patients, 18 (27.7%) were compliant and 47 (72.3%) were non-compliant with their prescribed antihypertensive medication. The recurrence of stroke was significantly higher in non-compliant patients, with 66.67% experiencing a second stroke, compared to 33.33% among compliant patients. Conclusion: There is a significant association between non-compliance with antihypertensive medication and both the onset and recurrence of stroke. Enhancing patient adherence to antihypertensive therapy through education and healthcare interventions is vital to reducing stroke-related morbidity and mortality.